(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The purpose of the study is to analyze the financial performance of Indian Pharmaceutical Acquirers and compare the pre- and post financial performance of acquirers conducting minority and majority acquisitions. The financial analysis was conducted on the data of 13 acquisition deals for the period between 2010 and 2019 by comparing the three-year pre- and post-acquisition periods until the year 2023 using the paired t-test methodology. The findings of the study revealed that there is no significant difference in the profitability and liquidity positions of the acquirers in the pre- and post-acquisition periods. Finally, the comparison between the financial performance of majority and minority acquisitions shows that the financial performance of acquirers deteriorates after the post-acquisition period, but the performance of majority acquisitions’ acquirers is still better when compared to minority acquisitions.